Implementasi Fungsi DPRD Provinsi Bali dalam Percepatan Penanganan Pandemi Covid-19 - Desak Putu Oka Hari Parwati (Public Inspiration : Jurnal Administrasi Publik, 2022)
This study took the title "Implementation of the Functions of the Bali DPRD in Accelerating the Handling of the Covid-19 Pandemic" against the background of the Covid-19 Pandemic that hit the world, including Indonesia. The Covid-19 pandemic brings many problems, therefore all elements of the nation have a responsibility to overcome them, including the Regional Legislative Council of Bali Provincial (DPRD) as the organizer of government in the region. The DPRD has a very important role in accelerating the handling of the Covid-19 pandemic. As is well known, DPRD has a very vital function, namely the legislative function, budget function, and supervisory function. The purpose of this study is to analyze, understand, and evaluate the extent to which the function of the Bali Provincial DPRD in accelerating the handling of the Covid-19 pandemic, as well as to analyze, understand, and evaluate the factors that hinder and encourage the function of the DPRD in accelerating the handling of the Covid-19 pandemic. The method used in data collection is observation and interviews, and supported by literature study. In processing data through several stages, namely: data collection, data reduction, data presentation and drawing conclusions and verification. The results of the study show that the implementation of the function of the Bali Provincial DPRD in accelerating the handling of the Covid-19 pandemic has gone well. This can be seen from the legislative function through a letter of recommendation from the Bali Provincial DPRD to the Governor of Bali to immediately issue regulations for handling the Covid-19 pandemic; budget function with the approval of budget refocusing and reallocation; and the supervisory function through field supervision activities as well as working visits carried out by each commission.